Respuestas

¡La mejor respuesta!
2013-11-13T18:12:11+01:00
3+2+1=-12
2-3+4=23
3+2+1          (3. -3 .1) + (2.2) + (2.4)+(3. -3 .1) + (2.2) +(2.4) = -18+24=6

buscamos X  -12 +2 +1
                     23 -3 +4
                    -12 +2 +1  (-12. -3 .1) + (23.2) + (2.4)(23.2) + (-12. -3 .1)+ (2.4)=
                                       36+46+8+46+36+8=180
buscamos Y  3 -12  1
                     2 23  4
                     3 -12  1 (3.23.1)+ (-12.4)+(2. -12)+(2. -12) + (3.23.1) +(-12.4)=
                                   69-48-24-24+69-48=-6
buscamos Z por sustitución
3X  +  2Y  +Z = -12
3.180 + 2. -1 + z = -12
540  -2  + z = -12
Z= -538-12
Z= -550

comprobación  3.180 +2 . -1 -550 = -12
                       540 - 2 - 550 = -12        -552 + 540=-12        -12 = -12